2011
DOI: 10.1021/la200038a
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and Physical Interactions between Novel Polymeric Surfactants and Lipids: Toward Designing Stable Polymer–Lipid Complexes

Abstract: Surfactant amphiphilic macromolecules (AMs) were complexed with a 1:1 ratio of 1,2-dioleoyl-3-trimethyl-ammonium-propane (DOTAP) and 1,2-dioleoyl-sn-glycero-3-phosphoethanolamine (DOPE), either by a coevaporation (CE) or postaddition (PA) method, to form AM–lipid complexes with enhanced drug delivery applications. By characterizing the surfactant–lipid interactions, these heterogeneous drug delivery systems can be better controlled and engineered for optimal therapeutic outcomes. In this study, the physical in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Liposomes and micelles can be regarded as potential drug delivery systems in research and industry . Consequently, numerous studies investigate novel micelle forming polymers as well as targeted uptake and release kinetics from nanostructured materials such as liposomes or micelles. One of the crucial factors, representing the capacity of potential drug delivery systems, is the partition coefficient of a potential drug candidate between the aggregate and the surrounding water. Depending on the hydrophobicity of the solute, it partitions into different regions of the aggregate.…”
Section: Introductionmentioning
confidence: 99%
“…Liposomes and micelles can be regarded as potential drug delivery systems in research and industry . Consequently, numerous studies investigate novel micelle forming polymers as well as targeted uptake and release kinetics from nanostructured materials such as liposomes or micelles. One of the crucial factors, representing the capacity of potential drug delivery systems, is the partition coefficient of a potential drug candidate between the aggregate and the surrounding water. Depending on the hydrophobicity of the solute, it partitions into different regions of the aggregate.…”
Section: Introductionmentioning
confidence: 99%
“…Lipid film was hydrated using 10 mM HEPES, MP Biomedical LLC (Aurora, OH, USA) for 1 mg/mL solutions with continuous shaking on an orbital reciprocating shaker for 1 h. Liposomes were produced by extruding through an Avanti mini-extruder system (Avanti Polar lipids) using 0.1 µm membrane filters, resulting in sizes averaging 100 nm after 21 passes. Liposomes were used within 10 h, stored at 4 °C [ 48 , 49 ]. Liposome sizes were measured using a Dynamic Light Scattering (DLS), NanoZS90 Instrument (Malvern Instruments, Malvern, UK).…”
Section: Methodsmentioning
confidence: 99%
“…The attractive intermolecular interaction between SBAP and lipid was illustrated by the observed condensation effect, in which the experimental molecular area negatively deviates from the ideal molecular area (i.e., no intermolecular interaction). These results indicated that SBAPs and lipids formed a stable mixture . To evaluate how serum impacts the size of SBAP–lipid complexes, dynamic light scattering (DLS) was used to monitor the complexes’ sizes over time.…”
Section: Liposomes: Stabilization and Drug Deliverymentioning
confidence: 97%
“…These results indicated that SBAPs and lipids formed a stable mixture. 23 To evaluate how serum impacts the size of SBAP− lipid complexes, dynamic light scattering (DLS) was used to monitor the complexes' sizes over time. Complexes with low SBAP content underwent visible aggregation upon serum addition.…”
Section: ■ Nanomicelles: Sbaps In Cancer Therapymentioning
confidence: 99%